Fiscal Policy and Credit Supply in a Crisis - Bonfim, Diana; Ferreira, Miguel A.; Queiró, Francisco; Zhao, Sujiao (Emma) (American Economic Review, 2025)
We measure how cuts to public procurement propagate through the banking system in a financial crisis. During the European sovereign debt crisis, the Portuguese government cut procurement spending by 4.3 percent of GDP. We find that this cut saddled banks with nonperforming loans from government contractors, which led to a persistent reduction in credit supply to other firms. We estimate a bank-level elasticity of credit supply with respect to procurement demand of 2.5. In a general equilibrium model, our findings point to large effects of fiscal policy on credit supply and output in a crisis. (JEL E23, E44, E62, G01, G21, H57)